The Effect of Covid 19 on Students’ Emotional Intelligence in Language Learning - Wildona Zumam; Mohammad Amiruddin; Nur Syakherul Habibi (IKIP PGRI Bojonegoro, 2023)
Abstract: The purpose of this study is to determine the impact of the COVID 19 pandemic on students' emotional intelligence in language acquisition. This is an experimental study that employs a quantitative method. In this study, students in higher education are treated as a subset of the population. The sampling size is determined using a random sampling approach. This study's subjects are 36 students. The paired t test approach is used to assess the data. The study's findings indicate that sig (p) is substantial. It is less than 0.05. (it is 0.000). The distinction can be deemed true. Before COVID 19, the mean was 59.30; after COVID 19, the mean was 49.33. It suggests that pupils prior to the COVID 19 pandemic had higher emotional intelligence in language acquisition than students after the epidemic. It implies that teachers and members of educational society in higher education are expected to provide students with a suitable environment in order to provide students with consequential input as well as provide students with interface in an attempt to maintain the regularity of experiencing English; additionally, it is suggested that members of scholar society are expected to provide significant input for the students. Keywords: Effect, COVID 19, Emotion, Intelligence, Learning Abstrak: Tujuan dari penelitian ini adalah untuk mengetahui dampak pandemi COVID 19 terhadap kecerdasan emosional siswa dalam pemerolehan bahasa. Penelitian ini merupakan penelitian eksperimental yang menggunakan metode kuantitatif. Dalam studi ini, mahasiswa di pendidikan tinggi diperlakukan sebagai bagian dari populasi. Sampel ditentukan dengan menggunakan pendekatan random sampling. Subyek penelitian ini berjumlah 36 siswa. Pendekatan uji t berpasangan digunakan untuk menilai data. Temuan studi menunjukkan bahwa sig (p) adalah substansial. Ini kurang dari 0,05. (ini adalah 0,000). Perbedaan itu bisa dianggap benar. Sebelum COVID 19, rata-ratanya adalah 59,30; setelah COVID 19, rata-ratanya adalah 49,33. Ini menunjukkan bahwa siswa sebelum pandemi COVID 19 memiliki kecerdasan emosional yang lebih tinggi dalam penguasaan bahasa daripada siswa setelah epidemi. Ini menyiratkan bahwa guru dan anggota masyarakat pendidikan di pendidikan tinggi diharapkan untuk menyediakan lingkungan yang cocok bagi siswa untuk memberikan siswa dengan masukan konsekuensial serta menyediakan antarmuka siswa dalam upaya untuk menjaga keteraturan mengalami bahasa Inggris; Selain itu, disarankan agar para civitas akademika dapat memberikan masukan yang signifikan bagi para mahasiswa. Kata kunci: Pengaruh, COVID 19, Emosi, Kecerdasan, Pembelajaran